SISTEM MONITORING PENGERING SEPATU BERBASIS INTERNET OF THINGS PADA PLATFORM NODE-RED - Yuli Murdianingsih; Lina Aprianti (STMIK SUBANG, 2021)
Shoes are one of the human equipment that must always be worn in conditions, including during the rainy season, and conventional shoe drying still faces several challenges, including relying on the help of sunlight to facilitate drying. Shoes are one of the human equipment that must always be worn in conditions, including during the rainy season. The goal of this research is to create a shoe dryer monitoring system using the Node-ed Platform and the Internet of Things. Light, temperature, and humidity are all monitored in shoes. Arduino Uno, NodeMC ESP8266, Breadboard, Jumper Cables (male-to-male, male-to-female, female-to-female), Arduino USB Cable, 2 Channel Relay, Incandescent Lamp, CPU Fan, Servo Motor, DHT11 Sensor, and LDR Sensor are the components needed to make this system. While the software, specifically Ardu, was used, While the software employed, specifically the Arduino IDE, allows the author to program the NodeMCU ESP8266, Arduino Uno, and other hardware components that will be used in this study. To write programs, you'll need a C program editor and compiler. The major component in the implementation of this research is the Node-red platform. The NodeMCU ESP8266 is used as a tool in this shoe dryer monitoring system, which leverages a wireless network architecture. The shoe dryer monitoring system can perform as intended as a result of this research; this tool can monitor light, temperature, and humidity in shoes in real-time, as well as deliver actions in the form of notifications via social media in the form of Telegram.